MODEL PEMBELAJARAN BLENDED LEARNING PASCA NEW NORMAL COVID-19 - Sy Rohana; Andi Syahputra (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
The teachers are required to be able to adapt and develop their learning model in post-new normal condition at this time, the model should make the students understand the material being taught easier. In addition, teachers must also be able to apply face-to-face (traditional) and non-face-to-face (online) models. Therefore, to solve the problem, there is an appropriate learning model, namely blended learning. This article aims to examine in-depth thinking about the implementation of this learning model with the literature review method. Indeed, the blended learning model is a learning process that utilizes various approaches (i.e., media and technology) both offline and online. moreover, it can improve students’ access in accessing learning materials, enhance their new experiences, improve the quality of learning, and reduce learning costs. As result, this article indicates that a theoretically blended learning model can be a learning model in post-new normal at the school and university, but further research is still needed to examine the effectiveness of blended learning implementation.